Erich Mercker and technical subjects a landscape and industrial artist in twentieth-century Germany - Jung, Patrick J. 1963-; Stahnke, Carma M. (MSOE Press, 2014)
This biography offers a thorough examination of Mercker's work within the larger context of German art history during the 20th century. According to the authors, this book was written for the general reader who is interested in learning more about Mercker and the artistic and historical contexts in which he lived and worked. As such, they provide the necessary background information concerning Germany and its rich artistic heritage to allow the reader to fully understand and appreciate Mercker's corpus of paintings